Odpowiedź:
a)
-4x - (5x + 3) - (-2x - 9) = -4x - 5x - 3 + 2x + 9 = -7x + 6
b)
- 9xy(2x - 5y + 8) = -18x²y + 45xy² - 72xy
c)
20a-10b-15 4a-8b+16
----------------- - ---------------- = 4a - 2b - 3 - a + 2b - 4 = 3a - 7
5 4
d)
3(2x - 8) + 7(4x - 9) = 6x - 24 + 28x - 63 = 34x - 87
e)
(bx - 9)(4x - 10) = 4bx² - 10bx - 36x + 90
f)
- 7(3x - 5)(4x - 8) = (-21x + 35)(4x - 8) = -84x² + 168x + 140x - 280 =
= -84x² + 308x - 280
g)
- 5x+(-2x+4)-7(9x-8)= -5x - 2x + 4 - 63x + 56 = -70x + 60
Szczegółowe wyjaśnienie: